Adult and Youth Involvement in Gun-Related Crime: Implications for Gun Violence Prevention Interventions - Circo, Giovanni (Criminal justice policy review, 2018)
The purpose of this study is to assess whether distinct targeted violence prevention programs are needed to address gun violence based on offender age. Police incident reports were used to analyze the temporal, situational, and spatial patterns of offending between a group of adult and youthful offenders in the city of Detroit, Michigan. Chi-square and logistic regression multivariate techniques were used to test the differences and similarities between these groups. The findings suggest that youth and adult offenders of gun crimes in Detroit are not significantly different in the time or place in which they offend. Only modest differences were observed in terms of situational characteristics. The most significant differences between youth and adult offenders involved the age of their victim and the presence of co-offenders. Policy implications are discussed.